2019
DOI: 10.3390/molecules24224084
|View full text |Cite
|
Sign up to set email alerts
|

Speciation Studies of Bifunctional 3-Hydroxy-4-Pyridinone Ligands in the Presence of Zn2+ at Different Ionic Strengths and Temperatures

Abstract: The acid–base properties of two bifunctional 3-hydroxy-4-pyridinone ligands and their chelating capacity towards Zn2+, an essential bio-metal cation, were investigated in NaCl aqueous solutions by potentiometric, UV-Vis spectrophotometric, and 1H NMR spectroscopic titrations, carried out at 0.15 ≤ I/mol −1 ≤ 1.00 and 288.15 ≤ T/K ≤ 310.15. A study at I = 0.15 mol L−1 and T = 298.15 K was also performed for other three Zn2+/Lz− systems, with ligands belonging to the same family of compounds. The processing of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The data presented in the current paper for Cu 2+ and Fe 3+ /(3-hydroxy-4-pyridinones) systems ( Table 1 and Table 2 ) were compared with those already reported in the literature on the interaction of the five ligands with Zn 2+ [ 19 ] and Al 3+ [ 13 ] ( Table S4 ) at I = 0.15 mol L −1 in NaCl (aq) and T = 298.15 K. The speciation models determined for the different systems display a common species, namely the M L (n-z) , which can be used as reference to evaluate and compare the binding ability of the ligands towards the metal cations. The data analysis showed that the log K 110 trend is: Fe 3+ > Al 3+ > Cu 2+ > Zn 2+ , meaning that the 3,4-HPs are featured by a much higher tendency to form very stable complex species with Fe 3+ , followed by Al 3+ , with respect to the M 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data presented in the current paper for Cu 2+ and Fe 3+ /(3-hydroxy-4-pyridinones) systems ( Table 1 and Table 2 ) were compared with those already reported in the literature on the interaction of the five ligands with Zn 2+ [ 19 ] and Al 3+ [ 13 ] ( Table S4 ) at I = 0.15 mol L −1 in NaCl (aq) and T = 298.15 K. The speciation models determined for the different systems display a common species, namely the M L (n-z) , which can be used as reference to evaluate and compare the binding ability of the ligands towards the metal cations. The data analysis showed that the log K 110 trend is: Fe 3+ > Al 3+ > Cu 2+ > Zn 2+ , meaning that the 3,4-HPs are featured by a much higher tendency to form very stable complex species with Fe 3+ , followed by Al 3+ , with respect to the M 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…The data analysis showed that the log K 110 trend is: Fe 3+ > Al 3+ > Cu 2+ > Zn 2+ , meaning that the 3,4-HPs are featured by a much higher tendency to form very stable complex species with Fe 3+ , followed by Al 3+ , with respect to the M 2+ . In addition, considering the stability constants reported in the literature for the Zn 2+ [ 19 ] and Al 3+ /(H 2 ( L2 ) , H( L5 )) systems [ 13 ], the pZn and pAl values were also calculated at physiological pH ( Table 4 ) and compared with the analogous results presented in this paper for Cu 2+ and Fe 3+ . Analysing the data obtained for the different metal cations and the graphs in Figure 10 and Figure S8 , we can conclude that, similarly to the log K 110 behaviour, the pM values follow the trend for the metal ions: Fe 3+ > Al 3+ > Cu 2+ > Zn 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordination compound formation in a solution depends on many factors such as stoichiometry, concentration, ionic strength, solvent type, and temperature [ 15 , 16 ]. Typically, different coordination species exist in an equilibrium in a solution, but not necessarily the dominant one can crystallize.…”
Section: Introductionmentioning
confidence: 99%
“…The Special Issue had satisfactory feedback from researchers, with contributions having cross-field character and being of interest for different industrial, pharmaceutical, chemical, and biological fields [7][8][9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%